Venomics reveals novel ion transport peptide-likes (ITPLs) from the parasitoid wasp Tetrastichus brontispae. (January 2018) - Liu, Nai-Yong; Xu, Zhi-Wen; Yan, Wei; Ren, Xue-Min; Zhang, Zhi-Quan; Zhu, Jia-Ying
Abstract: Despite substantial advances in uncovering constituents of parasitoid venoms due to their potential applications as insecticides and pharmaceuticals, most of these studies are primarily restricted to braconid and ichneumonid wasps. Little information is available regarding virulent factors from venom of Eulophidae. In order to provide insight into the venom components of this family and parasitoid venom evolution, a venom protein repertoire (venomics) of the endoparasitoid wasp, Tetrastichus brontispae was deciphered using a proteomic approach. A large number of diverse venom proteins/peptides were identified, including novel proteins and those proteins commonly found in the venoms of other parasitoids such as serine protease, esterase, dipeptidyl peptidase IV, acid phosphatase, major royal jelly protein, superoxide dismutase, and venom allergen 3/5. Three ion transport peptide-likes (ITPLs) were abundantly detected in T. brontispae venom. Of these, two of them are reported as a novel form for the first time, with the characteristics of lengthened amino acid sequences and additional cysteine residues. These venom ITPLs are obviously apart from other general members within the crustacean hyperglycemic hormone/ion transport peptide (CHH/ITP) family. It implies that they would evolve unique functions essential for parasitism success. Graphical abstract: Highlights: Venom components of T. brontispae were unraveled by proteomic analysis. New venom proteins and a number of venom proteins commonly found in other parasitoids were identified. Three ITPLs were revealed as toxins, of which two were a novel form.